Flora dynamics and the problem of vegetation cover safety in the Volga basin - Stepan Senator (Studia Ecologiae et Bioethicae)
The general data of flora dynamics in the Volga basin and problems of its protection are presented. The flora dynamics are characterized through a) introduction of alien or non-native species, b) disappearance of certain species, c) appearance of new taxons. The red book of the Volga basin is one of the tools useful for the protection of vegetable cover. The red book underlies the principles of protection of rare species through the preservation of their environment.